2022
DOI: 10.15414/ainhlq.2022.0016
|View full text |Cite
|
Sign up to set email alerts
|

Priestia Endophytica Bacteria Stimulate Rhodiola rosea L. in vitro Growth

Abstract: Soil microorganisms, in particular so-called plant growth promoting rhizobacteria (PGPR), can positively affect plants, stimulating growth by changing their metabolism. In addition, these bacteria synthesize hormone-like chemicals that can influence the formation of primary roots. This work was aimed to determine the possibility of using the sterile cell-free cultural medium obtained after the growth of endophytic bacteria Priestia endophytica UKM B-7515 strain (test solution) to stimulate the rooting of a val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Alginite, as a natural rock, contains essential nutrients such as macro-and micronutrients [45,46]. By adding alginite to the soil, these nutrients can be supplied to plants, leading to their healthier growth, increased productivity and condition [47][48][49]. Zhao et al [43,50] observed that alginite significantly reduces the activity of stress enzymes, catalase, and peroxidase, indicating potential damage to the plant's defense system.…”
Section: Introductionmentioning
confidence: 99%
“…Alginite, as a natural rock, contains essential nutrients such as macro-and micronutrients [45,46]. By adding alginite to the soil, these nutrients can be supplied to plants, leading to their healthier growth, increased productivity and condition [47][48][49]. Zhao et al [43,50] observed that alginite significantly reduces the activity of stress enzymes, catalase, and peroxidase, indicating potential damage to the plant's defense system.…”
Section: Introductionmentioning
confidence: 99%